2012
DOI: 10.1016/j.jep.2011.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic protective effect of astragaloside IV–tetramethylpyrazine against cerebral ischemic-reperfusion injury induced by transient focal ischemia

Abstract: This study showed that ASG IV-TMPZ played a pivotal synergistic protective role against focal cerebral ischemic reperfusion damage in a rat experimental model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 34 publications
1
47
0
1
Order By: Relevance
“…AS-IV, as one of its active elements, has been revealed its pharmacological mechanisms to some degree. Recent researches have suggested that AS-IV might protect from cardiomyopathy via diverse effects upon a variety of intracellular signaling pathways, including the activation of Src/mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase (ERK) pathway, 22) inhibiting tumor growth factor (TGF)-β1 23) and ERK1/2 signaling pathways, 24) upregulating superoxide dismutase-1 levels, 3,25) antioxidative and nitric oxide-inducing pathway, 26) and improving intracellular calcium handling. 27,28) The aim of our study is to clarify the basic electrophysiological effects of AS-IV on cardiac myocytes, and we have found that AS-IV prolonged APd, and decreased I K and I CaL in guinea-pig cardiac myocytes.…”
Section: Effects Of As-iv On Na + Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…AS-IV, as one of its active elements, has been revealed its pharmacological mechanisms to some degree. Recent researches have suggested that AS-IV might protect from cardiomyopathy via diverse effects upon a variety of intracellular signaling pathways, including the activation of Src/mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase (ERK) pathway, 22) inhibiting tumor growth factor (TGF)-β1 23) and ERK1/2 signaling pathways, 24) upregulating superoxide dismutase-1 levels, 3,25) antioxidative and nitric oxide-inducing pathway, 26) and improving intracellular calcium handling. 27,28) The aim of our study is to clarify the basic electrophysiological effects of AS-IV on cardiac myocytes, and we have found that AS-IV prolonged APd, and decreased I K and I CaL in guinea-pig cardiac myocytes.…”
Section: Effects Of As-iv On Na + Currentsmentioning
confidence: 99%
“…antioxidation, [3][4][5] antivirus, 6,7) anti-apoptosis, 8,9) anti-hyperglycemic, 10,11) neuroprotection, 13) gastroprotection, 14) anti-chronicasthma, 15) and anti-lung-cancer. 16) One of AS-IV's targets is the cardiovascular system, and especially the heart.…”
mentioning
confidence: 99%
“…For decades, it has been widely used to treat cardiovascular and cerebrovascular diseases (Cai et al, 2000;Li et al, 2004;Chen et al, 2011;Yang et al, 2012), pulmonary hypertension (Tang et al, 1988;Jian-Sheng et al, in press), chronic renal failure (Cao et al, 1997), and cirrhosis (Li et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Overwhelming evidences have accumulated implying that excessive reactive oxygen species (ROS) and oxidative stress play key roles in the pathophysiology of I/R injury [13]. Normally, there is a balance between the formation of ROS and its consumption by the endogenous protective systems.…”
Section: Discussionmentioning
confidence: 99%